Behaviour Phenotyping of Parkinson’s Disease Animal Models Using Inertial Sensors - Saraiva, Tatiana Margarida Lança (2021)
Tese de mestrado Bioquímica (Bioquímica Médica) Universidade de Lisboa, Faculdade de Ciências, 2021